2012
DOI: 10.1007/s12263-012-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins protect human endothelial cells from mild hyperoxia damage through modulation of Nrf2 pathway

Abstract: The detrimental effects of high oxygen supplementation have been widely reported. Conversely, few is known about the effects of exposure to mild hyperoxic conditions, an interesting issue since the use of oxygenenriched mixture is now increasingly used in clinical practice and especially for professional and recreational reasons. Our study investigated if in vitro exposure of human umbilical vein endothelial cells (HUVECs) to moderate hyperoxia (O 2 32 %) induces cellular alterations, measured as changes in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 27 publications
5
40
0
2
Order By: Relevance
“…Moreover, treatment with C3G alone lead to an increase of GSH levels, supporting the hypothesis that it can induce “per se” an adaptive cell response associated with an increased reducing intracellular capacity, as seen for SOD activity. These data are in agreement with other reports, suggesting that specific flavonoids induce an increase of cellular antioxidant activity, and that such capability is the main property of these biocompounds .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, treatment with C3G alone lead to an increase of GSH levels, supporting the hypothesis that it can induce “per se” an adaptive cell response associated with an increased reducing intracellular capacity, as seen for SOD activity. These data are in agreement with other reports, suggesting that specific flavonoids induce an increase of cellular antioxidant activity, and that such capability is the main property of these biocompounds .…”
Section: Resultssupporting
confidence: 94%
“…Similarly, in accordance with our findings, other studies have demonstrated that pharmacological activation of Nrf2 transcription factor by different phenolic compounds (e.g., sulforaphane) induces antiatherogenic effects in vascular endothelium by suppressing inflammation [37]. Furthermore, in HUVECs, anthocyanin metabolites appeared able to activate Nrf2 pathway, through the involvement of ERK1/2 eliciting a protective effect in endothelium exposed to mild hyperoxia [27]. In our experiments, as consequence of Nrf2 activation, HO-1 and NQO-1 expression were upregulated following C3G pretreatment; this effect was present both in cells exposed or not to TNF-␣ (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The pretreatment with C3G was able, in a dose-dependent way, to significantly protect HUVECs from PA-induced toxicity. C3G, at the tested concentrations, and WEL alone did not affect cell viability, as reported elsewhere (Anwar et al, 2014;Cimino et al, 2013;Speciale et al, 2013). It is interesting that, at similar doses, in cultured…”
Section: C3g Protects Huvecs From Pa-induced Injurysupporting
confidence: 86%
“…Increased Nrf2 activity and improved mitochondrial function may both bolster its positive effects (MartinMontalvo et al 2011). Cimino et al (2013) reported that anthocyanins protect human endothelial cells from mild hyperoxic damage via the modulation of the Nrf2 pathway. Tea flavonoids also protect endothelial cells against inflammation by inhibiting AhR and activating Nrf2-regulated genes (Han et al 2012).…”
Section: Activators Of Nrf2/keap1-are Pathways As Clinical Therapeutimentioning
confidence: 99%